ANALISIS PENYERANGAN SOCIAL ENGINEERING - Rafizan, Onny (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2011)
In the era of Information where the Information itself has became one of valuable asset for an organization so, an organization will tried to protect the information that they have. But, even the thickest wall of security can fall if the people inside the security wall make mistake that leads to security hole. This kind of mistake usually can be exploit by hacker using Social Engineering. This research is trying to explore this type of attack by analyzing, gathering literature, and finding similar incident that already happen before, to give other people information about Social Engineering and the threat that this type of attack can pose. The result of this research will be recommendation that can be used to protect the companys information from the threat that comes from Social Engineering.